First Report of Banana Bunchy Top Disease on Banana in Bengkulu. - Mimi Sutrawati; Sempurna Ginting (Badan Penerbitan Fakultas Pertanian (BPFP), 2020)
Banana is a horticulture crop that has economic value and is widely cultivated in tropical countries. Banana production in Bengkulu province reached 259,748 quintals, then durian (110,387 quintals), tangerines (94,396 quintals) (BPS 2015). Banana bunchy top disease caused by Banana bunchy top virus (BBTV) infection is considered the most crucial virus disease affecting yield losses of a banana plantation in Asia, Africa, and the South Pacific. However, the incidence and molecular characters of BBTV has never been reported in Bengkulu. This research aims to characterize symptom variations, disease incidence, and disease severity of BBTV infection in Bengkulu and virus detection using molecular methods by polymerase chain reaction (PCR). Disease incidence of BBTV was measured based on field symptoms. The disease survey was conducted in Bengkulu city, Bengkulu Utara district, and Rejang Lebong district. The study showed that the incidence of BBTV in Bengkulu City, Bengkulu Utara, and Rejang Lebong ranged from 0% to 100%. The most common symptoms observed in the field involved vein clearing, upturned leaf, chlorotic, and ragged margins, reducing petiole length, distance, lamina width, and stunting. Banana crops that are infected with BBTV in the vegetative phase will not produce fruit. In contrast, viral infection in the generative phase causes the formation of stunted fruit that is not suitable for harvesting. Thus, the potential loss of yield due to stunted disease can reach 100%. This study's results are the first reports of BBTV infection in banana crops in Bengkulu. Disease diagnosis will form the basis of disease control strategies in banana crops.